Constructing the Citizen: The Primrose League and the Definition of Citizenship in the Age of Mass Democracy in Britain, 1918-1928 - Hendley, Matthew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractThe Primrose League was a patriotic mass organisation nominally independent from, but allied to the British Conservative Party. During the last quarter of the nineteenth century, it politically mobilised large numbers of British women. In addition, through its social activities, the League assisted with the social integration of those holding full political rights with those who did not. The Fourth Reform Act of 1918 fundamentally altered the structure of British politics by tripling the size of the electorate and giving the vote to a significant number of British women for the first time. In this new political environment, Conservatives were concerned with countering the rising Labour Party and limiting the expectations of new voters. After 1918, the Primrose League attempted to define or construct a partisan model of citizenship. The League's model emphasised citizens' duties, individuals' civil rights and the idea of active citizenship. This campaign both helped the Conservative Party to adjust to the new political order and gave the Primrose League a new role to play in the age of mass democracy.